Assessment of Schools, Change and Innovation of Leadership Processes and School Work Management - a Meta-Analysis Drawn from Official Reports - RAMALHO, Henrique Pereira (Faculdade de Filosofia e Ciências, 2017)
Under the yoke of change and innovation in the processes of leadership and management of school work drawn by the normative spectrum of the Law n.º 31/2002, of 20 December, our analysis has the first objective of understanding the official discourse around the role of those leaders, taking into account the criteria, attributes, indicators and assertions that mark their architecture according to the following categories and respective domains of indicators: i) school organization and management; ii) strategic planning; iii) self-regulation and improvement of educational action. A second objective is to analyze the centralities that this conception emphasizes, in order to (re) interpret the official discourse on the change and innovation of educational leadership and management within Portuguese schools. Methodologically, we proceed to a systematic meta-analysis (EGGER; SCHNEIDER; DAVEY-SMITH, 1998; CASTRO, 2001; ZIMMER, 2004) of content to the corpus of seven annual reports on the external evaluation of schools, covering the period between the 2006-2007 and 2012-2013. Interpretatively, the rationality explained by the official discourse raises the obligation to present innovative procedures and results in the image of a central evaluation framework, adding a minimalist and instrumental vision of the curricular and pedagogical leaderships of the periphery. Recebido em: 24 de outubro de 2016.Aceito em: 10 de outubro de 2017.